Quantitative Trait Loci Mapping Of Philippine Downy Mildew Resistance Gene In Maize (Zea Mays L.) - D. Ruswandi; D. M. Hautea; A. L. Carpena; R. M. Lantican; A. M. Salazar; A. D. Raymundo (Zuriat, 2002)
An experiment to locate QTL conferring resistance against Peronosclerospora philippinensis causing Philippine downy mildew was observed in a BC1F2 population developed from a cross between the susceptible inbred line Pi 23 and the resistant inbred line P 345. Phenotypic data were collected in Los Baños, UPLB for disease incidence. A total of four regions were associated with disease incidence. Some of QTL associated with disease incidence have been reported previously, and the remaining QTL are described here for the first time. The results on QTL analysis using molecular markers also agree with the previous study using classical generation mean analysis of the cross combination Pi 23 x P 345.